A TNF receptor loop peptide mimic blocks RANK ligand–induced signaling, bone resorption, and bone loss - Aoki, Kazuhiro (American Society for Clinical Investigation, 2006)
Activating receptor activator of NF-κB (RANK) and TNF receptor (TNFR) promote osteoclast differentiation. A critical ligand contact site on the TNFR is partly conserved in RANK. Surface plasmon resonance studies showed that a peptide (WP9QY) that mimics this TNFR contact site and inhibits TNF-α–induced activity bound to RANK ligand (RANKL). Changing a single residue predicted to play an important role in the interaction reduced the binding significantly. WP9QY, but not the altered control peptide, inhibited the RANKL-induced activation of RANK-dependent signaling in RAW 264.7 cells but had no effect on M-CSF–induced activation of some of the same signaling events. WP9QY but not the control peptide also prevented RANKL-induced bone resorption and osteoclastogenesis, even when TNFRs were absent or blocked. In vivo, where both RANKL and TNF-α promote osteoclastogenesis, osteoclast activity, and bone loss, WP9QY prevented the increased osteoclastogenesis and bone loss induced in mice by ovariectomy or low dietary calcium, in the latter case in both wild-type and TNFR double-knockout mice. These results suggest that a peptide that mimics a TNFR ligand contact site blocks bone resorption by interfering with recruitment and activation of osteoclasts by both RANKL and TNF.